Exploring Approaches to the Generation and Representation of Heritage Artefacts in Video Game Contexts. (June 2016) - Balela, Majed S.; Mundy, Darren
Video games can allow players to explore environments, which are representative of, or contain elements of physical world cultures, for example, allowing a player to explore ancient Egypt in Pharaoh (Impressions Games, 1999, Pharaoh [PC Game]. Sierra Entertainment) or present day Chicago in Watchdogs (Ubisoft Montreal, 2014, [PlayStation 4 game]. Guildford), etc. Game designers need to make design decisions regarding how these environments are going to be represented, including which items are going to be utilized, how they are going to be used in the game, and the level of detail to which they are going to be presented. These decisions can lead to concerns regarding how particular cultures are represented. This article describes research undertaken to investigate the design process with respect to the inclusion of physical world cultures in virtual game environments. Within the study approaches used (including processes and methods) by game designers in the stages of conceptualization, design and delivery are explored. In addition, these are contextualized through an understanding of designer attitudes towards the inclusion of items with cultural meaning and their perspectives on the importance of cultural representation within video games. This involved interviewing eight video game designers from global contexts within the industry, all with the experience of generating cultural items for inclusion in video game contexts. These interviews were structured with a focus on exploring views, experiences, beliefs and motivations of the individuals and of their working teams. Analysis was carried out through the use of a methodological process of analytical induction with the coding of particular variables within each interview transcript, and the transformation of the complete set of codings into a set of conceptual statements. This article relates these conceptual statements to earlier work regarding close readings of particular video games and discusses the relationship between design processes (facilitated through the interviews) and realized game worlds (facilitated through the close readings).